Cloud-Based UAV Monitoring and Management Framework - Chen, Chi; Shi, Dianxi; Cui, Shuyao; Kang, Yaru (2018 3rd International Conference on Control, Robotics and Cybernetics (CRC), 2018)
As an emerging technology, unmanned aerial vehicles(UAVs) are quietly changing people's lives and may revolutionize the commercial and industrial sectors. Because of the characteristic of long-time, high-intensity, high-precision, and adaptability to harsh working environments, UAVs not only have applications such as investigations in the military field, but also have developed in areas such as natural disaster relief and logistics distribution. With the increase in the number of military UAVs and commercial UAVs, the management and monitoring of multiple UAVs is particularly important. The monitoring and management of UAVs involves many technologies such as image processing, wireless transmission, and remote monitoring. It has great technical challenges for research and is currently a hot international research topic. In this paper, we propose an innovative cloud-based service-oriented UAVs monitoring and management framework to provide real-time flight monitoring and management for UAVs. We register and connect UAVs through the HTTP interface provided by the framework. For each connected UAV, data from the GPS sensor, altitude sensor, angular velocity sensor, gyro sensor, etc. represents the internal state of the UAV, the framework provides a real-time visual display. The real-time annotation of the position and path information of the UAV through the dynamic map enables the user to easily realize the monitoring and management of the multiple UAVs. This framework solves the problem of using UAVs through the Internet and proves its feasibility and performance through simulation.